Design And Development Of Oral Antihyperglycaemic Formulations For Water-Soluble Palm Fruit Extract - Dayoob, Mohamad (2022)
Water-soluble palm fruit extract (WSPFE) is recovered from the palm oil production waste stream in Malaysia. WSPFE consists of valuable water-soluble phenolic acids including protocatechuic acid (PCA), p-hydroxybenzoic acid (p-HBA), and three isomers of caffeoyl-shikimic acid. WSPFE demonstrated several therapeutic activities in vitro and in vivo. However, the high sugar content of WSPFE may lead to gastrointestinal side effects, likely resulting in compliance issues. Also, the lower phenolic content compared to the sugar content means that a large quantity of WSPFE should be consumed to achieve the therapeutic effects. Different methods were used to remove the sugars and extract the phenolic acids in WSPFE, namely liquid-liquid extraction (LLE), ethanolic precipitation, alkaline hydrolysis, and solid phase extraction (SPE) by using Amberlite XAD-2 and Oasis HLB resins. The most efficient method for removing the sugars and extracting the phenolics was found to be through SPE by Oasis HLB, followed by Amberlite XAD-2. The sugar-removed WSPFE (SR-WSPFE) samples were examined in vitro using different assays. The highest antioxidant, alpha-amylase inhibition, and alpha-glucosidase inhibition activities were observed in SR-WSPFE that was extracted by Oasis HLB, followed by Amberlite XAD-2. Therefore, the SR-WSPFE obtained by using Oasis HLB was chosen for further product development process. Preformulation studies revealed some drawbacks of SR-WSPFE including hygroscopicity, high moisture content, bitter taste, and poor flow properties. Different carriers and formulation approaches were applied to overcome the problems of SR-WSPFE.